2015
DOI: 10.1590/0074-02760140332
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic switching: from antidermatophytic essential oils to new leishmanicidal products

Abstract: This study examined whether the antidermatophytic activity of essential oils (EOs) can be used as an indicator for the discovery of active natural products against Leishmania amazonensis. The aerial parts of seven plants were hydrodistilled. Using broth microdilution techniques, the obtained EOs were tested against three strains of dermatophytes (Trichophyton mentagrophytes, Microsporum gypseum and Microsporum canis). To compare the EOs antifungal and antiparasitic effects, the EOs activities against axenic am… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
27
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 32 publications
(30 citation statements)
references
References 36 publications
2
27
0
1
Order By: Relevance
“…The essential oil of the aerial parts of Piper auritum had CC 50 values of 106.4 ± 3.4 µg/mL against peritoneal macrophages from BALB/c mice [32]. Piper hispidum had a CC 50 value of 35.5 µg/mL against peritoneal macrophages from BALB/c mice and CC 50 > 100 against Vero cells [33]. The present study found higher values, which may be due to differences in the chemical composition of the oils and due to different assay conditions used.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The essential oil of the aerial parts of Piper auritum had CC 50 values of 106.4 ± 3.4 µg/mL against peritoneal macrophages from BALB/c mice [32]. Piper hispidum had a CC 50 value of 35.5 µg/mL against peritoneal macrophages from BALB/c mice and CC 50 > 100 against Vero cells [33]. The present study found higher values, which may be due to differences in the chemical composition of the oils and due to different assay conditions used.…”
Section: Resultsmentioning
confidence: 99%
“…Studies carried out with the essential oil of Piper hispidum identified an IC 50 of 3.4 µg/mL against amastigote forms of Leishmania amazonensis [33]. The leishmanicidal activity of the essential oils is due to the presence of terpenoids, which have demonstrated antiparasitic activity against a range of species of Leishmania [34].…”
Section: Resultsmentioning
confidence: 99%
“…Promising antiplasmodial activity was reported for extracts from P. capense [268], P. cumanense [170] and P. nigrum [272], with IC 50 values of 2 µg/mL, 7 μg/mL and 12.5 μg/mL, respectively. In contrast, antitrypanosomal and antileishmanial potentialities were prominent in the EO from P. aduncum [45] with IC 50 values of 2.8 μg/mL, 12.1 μg/mL and 9 μg/mL in cell-derived and metacyclic trypomastigotes, as well as intracellular amastigotes, and P. malacophyllum with 17 μg/mL against trypomastigotes [273] of T. cruzi ; while oil from P. demeraranum with IC 50 value of 15 µg/mL [93] and P. hispidum with 4.7 µg/mL value [274] against Leishmania amazonensis .…”
Section: Antiparasitic Activities Of Piper Speciesmentioning
confidence: 99%
“…Piper auritum EO inhibits the proliferation of promastigotes of Leishmania major , L. mexicana , L. braziliensis and L. donovani , with IC 50 values (for 72 h treatments) between 12.8 and 63.3 µg/mL ( Monzote et al 2010) . Also P. hispidum EO showed promising results (high antileishmanial activity with low cytotoxicity, and a safety index of eight) when treating L. amazonensis -infected macrophages ( Houël et al 2015) . The EO of P. cubeba was not active against L. amazonensis , but was effective against T. cruzi , with IC 50 values of 45.5 and 87.9 µg/mL, for trypomastigote and amastigote forms, respectively ( Esperandim et al 2013) .…”
mentioning
confidence: 99%